Cardiac tamponade due to pneumopericardium. Issue 6 (June 1988) - Johnston, S L; Oliver, R M
Abstract : Pneumopericardium is rare in acute asthma and cardiac tamponade has not been reported. The case is reported of a 20 year old asthmatic patient in whom assisted ventilation and high airway pressures resulted in tension pneumopericardium with clinical signs of cardiac tamponade that were relieved by pericardial aspiration.